Inconsistent, vague, and…just? An analysis of the National Football League`s 2021 COVID-19 policy - Gimbel, S.; Radzevick, J. (Philosophies, 2022)
The National Football League, the premier professional organization for American football, developed a policy concerning the protocol in cases where players contract COVID-19. This policy includes elements such as collective punishment that appear, at first glance, to be morally problematic. To the contrary, the policy is indeed morally acceptable as we should not think of organizations such as the NFL in the same way we think of governments in stable nations, but rather in the same way that we think of hybrid justice systems in countries where because of histories of colonialism, the identity of citizens is divided, with tribal identities being more important than national citizenship.